Multiple Factors Affecting on the Memory and Forgetting Process: Its Effects on Academic Performance of Children (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Memory is an important cognitive function that plays a significant role in students’ academic achievement. It is not a simple process but consists of learning, retaining, recalling and recognizing ability of the children. It refers to the remembering that a child has previously acquired or learnt and assists a child in forcing the previous knowledge to come out into a conscious state in the form of image and ideas etc. Memory involves three major processes: encoding, storage, and retrieval. Good memory indicates good academic performance, because students can utilize their maximum abilities in their studies that will lead them near to bright success. So, it indicates that there is a positive correlation between memory and academic performance. The aim of the present endeavour is to be familiar with terms of memory as well as forgetting, and also to find out those factors which are considered responsible to boost up good memory and also those factors which are considered responsible for the forgetting process.